Wake up to the screens: Digital consumption in the adult population at the beginning of the day and perceived opportunity cost - Picazo Sánchez, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
A study is presented carried out on an adult population of 447 people in Spain who self-critically recorded their digital consumption when they woke up in the morning, still in bed. The analysis instrument includes a total of 67 parameters related to the device, content consulted and perceived cost-opportunity, which involved 29,949 open responses. The results show that, upon waking up, people turn to their smartphone to consult WhatsApp, the alarm app and Instagram, sacrificing sleep time, better organization, starting the day calmly and doing sports. Society must integrate attention economy and digital self-criticism as educommunicative practices.